Challenges in the Investigation Process when Interfering with the Right to the Inviolability of Private Life (On the Example of Search and Seizure) - Levan Darbaidze (European Scientific Journal, ESJ, 2026)
Criminal law cannot exist without human rights law. Every investigative or procedural action inherently involves a certain degree of interference with fundamental human rights, which may be carried out only with particular caution and exclusively for the purpose of achieving a legitimate aim. Such interference must, at the same time, be suitable, necessary, and proportionate. The court is entrusted with the function of the so-called “review” of decisions made by the investigative authority. It is precisely this authority of the court that constitutes the principal component of the legal mechanism through which the prevention of unjustified interference with fundamental human rights must be ensured. This risk becomes particularly evident where, in cases of urgent necessity, in order to discover an object, document, substance, or other item containing information relevant to the case, it is necessary to conduct a search/seizure. The present article addresses the scientific analysis of investigative and judicial practice existing at both national and international levels in this regard, the purpose of which is to identify challenges and to seek ways to overcome them.